Altitude Travel in Patients With Pulmonary Hypertension: Randomized Pilot-Trial Evaluating Nocturnal Oxygen Therapy - Lichtblau, Mona; Saxer, Stéphanie; Latshang, Tsogyal D.; Aeschbacher, Sayaka S.; Huber, Fabienne; Scheiwiller, Philipp M.; Herzig, Joël J.; Schneider, Simon R.; Hasler, Elisabeth D.; Furian, Michael; Bloch, Konrad E.; Ulrich, Silvia (Frontiers in Medicine, 2020)
Introduction Stable patients with pulmonary arterial or chronic thromboembolic pulmonary hypertension (PH) wish to undergo altitude sojourns or air travel but fear disease worsening. This pilot-study investigates health effects of altitude sojourns and potential benefits of nocturnal oxygen therapy (NOT) in PH-patients. Methods Nine stable PH-patients, age 65 (47;71), 5 women, in NYHA class II, on optimized medication, were investigated at 490m and during two sojourns of two days/nights at 2048m, once using NOT, once placebo (ambient air), 3L/min per nasal cannula, according to a randomized cross-over design with 2 weeks washout at <800m. Assessments included safety, nocturnal pulse oximetry (SpO2), 6-minute walk distance (6MWD) and echocardiography. Results At 2048m, 2 of 9 patients required medical intervention, one for exercise-induced syncope, one for excessive nocturnal hypoxemia (SpO2<75% for >30min). Both recovered immediately with oxygen therapy. 2 patients suffered from acute mountain sickness. In 6 patients with complete data, nocturnal mean SpO2 and cyclic SpO2 dips reflecting sleep apnea significantly differed from 490m to 2048m with placebo, and 2048m with NOT (medians, quartiles): SpO2 93(91;95)%, 89(85;90)%, 97(95;97)%; SpO2 dips 10.4/h(3.1;26.9), 34.0/h(5.3;81.3), 0.3/h(0.1;2.3). 6MWD at 490m, 2048m without and with NOT was: 620m (563;720), 583m(467;696) and 561m(501;688). Echocardiographic indices of heart function and PH were unchanged at 2048m with/without NOT vs. 490m. Conclusions 7/9 PH patients stayed safely at 2048m but revealed hypoxemia, sleep apnea and reduced 6MWD. Hemodynamic changes were trivial. NOT improved oxygenation and sleep apnea. The current pilot-trial is import for designing further studies on altitude tolerance of PH-patients.